EVALUASI PENGENDALIAN BIAYA DENGAN METODE CRITICAL PATH METHOD (CPM) MENGGUNAKAN MICROSOFT PROJECT - Mohammad Rizal Mantovani; Michella Beatrix (LPPM Universitas Bina Bangsa, 2023)
In the implementation of a project sometimes it does not go well, because there are obstacles that hinder the existing work. One of the obstacles that are often encountered in the field in the Tanjung Perak Diamond Pier Structure Strengthening project in Surabaya is uncertain weather conditions, this is because in carrying out the initial planning the planners did not consider the weather conditions that would occur during the implementation of this project. The impact that arises due to this delay is the increase in the duration and budget for the implementation of the project. So that in overcoming this, rescheduling is carried out which is expected to produce a logical and realistic schedule as well as costs that are as expected. The purpose of this study is to calculate the results of the costs needed in implementing the project after rescheduling. This type of research is analytic in nature. Data collection in the form of secondary data such as schedules and Budget Plans (RAB) is carried out by directly requesting the required data from related parties, then evaluating the initial costs, followed by preparing new costs using Microsoft Project tools using the Critical Path Method (CPM)). The results of this study obtained a total rescheduling fee of Rp. 28,535,441,605, there is a difference in costs of Rp. 6,482,544,691.1 of the initial planned cost of Rp. 35,017,986,296.10